A Pregnant Woman Who Underwent Laparoscopic Adrenalectomy due to Cushing's Syndrome - Diri, Halit; Bayram, Fahri; Simsek, Yasin; Ozkan, Yusuf; Akcan, Alper; Karahan, Ibrahim; Koc, Mehmet Sait (Hindawi Ltd, 2014)
Cushing's syndrome (CS) may lead to severe maternal and fetal morbidities and even mortalities in pregnancy. However, pregnancy complicates the diagnosis and treatment of CS. This study describes a 26-year-old pregnant woman admitted with hypertension-induced headache. Hormonal analyses performed due to her cushingoid phenotype revealed a diagnosis of adrenocorticotropic hormone-(ACTH-) independent CS. MRI showed a 3.5 cm adenoma in her right adrenal gland. After preoperative metyrapone therapy, she underwent a successful unilateral laparoscopic adrenalectomy at 14-week gestation. Although she had a temporary postoperative adrenal insufficiency, hormonal analyses showed that she has been in remission since delivery. Findings in this patient, as well as those in previous patients, indicate that pregnancy is not an absolute contraindication for laparoscopic adrenalectomy. Rather, such surgery should be considered a safe and efficient treatment method for pregnantwomenwith cortisol-secreting adrenal adenomas.
Keywords: Cortisol; Adenoma; Plasma; Management; Diagnosis; Secondary; Axis